Digital Literature and Critical Theory - Elstermann, Annika (Taylor & Francis, 2023)
The aim at the core of this book is a synthesis of increasingly popular and culturally significant forms of digital literature on the one hand, and established literary and critical theory on the other: reading digital texts through the lens of canonical theory, but also reading this more traditional theory through the lens of digital texts and related media. In a field which has often regarded the digital as apart from traditional literature and theory, this book highlights continuities in order to analyse digital literature as part of a longer literary tradition. Using examples from social media to video games and works particularly by postmodern and poststructuralist theorists, Digital Literature and Critical Theory contextualises digital forms among their analogue precursors and traces ongoing social developments which find expression in these cultural phenomena, including power dynamics between authors and readers, the individual in (post-)modernity, consumerism, and the potential for intersubjective exchange.